2022
DOI: 10.3389/fendo.2022.957301
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, hormonal and pathomorphological markers of somatotroph pituitary neuroendocrine tumors predicting the treatment outcome in acromegaly

Abstract: Background: Transsphenoidal adenomectomy (TSS) of somatotroph pituitary neuroendocrine tumor (PitNET) is the first-line treatment of acromegaly. Pharmacological treatment is recommended if surgery is contraindicated or did not lead to disease remission. The choice of treatment best fitting each patient should be based on thorough investigation of patients' characteristics. The current analysis attempts to create a tool for personalized treatment planning.Aim: This study aimed to assess whether clinical, bioche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 67 publications
1
6
1
1
Order By: Relevance
“…We found that lower absolute IGF-1 levels at diagnosis were associated with biochemical control after surgery at short-term in corroboration with other studies [ 11 , 30 , 31 ], but not with IGF-1/ULN and not at long-term follow-up. Thus, we do not regard this finding as a helpful predictor of biochemical control.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found that lower absolute IGF-1 levels at diagnosis were associated with biochemical control after surgery at short-term in corroboration with other studies [ 11 , 30 , 31 ], but not with IGF-1/ULN and not at long-term follow-up. Thus, we do not regard this finding as a helpful predictor of biochemical control.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, we did not find any variables associated with biochemical control at long-term. Of the few studies reporting long-term follow-up data exceeding three years postoperatively, preoperative GH and IGF-1 levels, tumor size and invasiveness, and age at diagnosis were among factors predicting long-term biochemical control after surgery [ 11 , 17 , 30 , 31 , 33 ]. Presurgical medical treatment may improve control rates [ 15 ], but medical pretreatment as a systematic approach in unselected patients remains controversial [ 8 , 9 , 15 , 22 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] Previous study has reported that the lower the GH level of acromegaly patients before treatment, the better the prognosis. [17] But due to the different degree of damage to pituitary function after apoplexy, this pattern was not found in our study.…”
Section: Discussioncontrasting
confidence: 73%
“…Surgical treatment can effectively lead to biochemical control. Furthermore, baseline characteristics that can impact long-term outcomes include age at diagnosis ( 7 ), gender ( 7 ), preoperative serum levels of GH and IGF-1 ( 8 - 13 ), preoperative medication ( 12 ), tumor size ( 8 , 9 , 12 ), invasiveness ( 12 , 14 ), Knosp grading scores ( 8 , 9 , 12 ), and histological pathology [Ki-67, somatostatin receptor subtype 2 expression, arylhydrocarbon receptor inter acting protein (AIP) expression, and granularity] ( 14 ). Therefore, identifying independent factors that predict long-term outcomes, such as biochemical remission or recurrence, may be crucial in facilitating clinical management.…”
Section: Introductionmentioning
confidence: 99%